Electronic reconstruction and surface two-dimensional electron gas in a polarized heterostructure with a hole-doped single copper-oxygen plane - Yang, Xiaoping (2013)
We show that confinement together with intrinsic polarization induce hole doping of the CuO2 plane in the proposed SrTiO3/[SrO-La2CuO4-SrO]/LaAlO3 heterostructure without resorting to chemical substitution, using the generalized gradient approximation and its combination with Coulomb correlation U. Hole concentration can be rationally manipulated via tuning the LaAlO3 thickness and in-plane strain. The stable antiferromagnetic insulating bulk state up to 8% doping in this disorder-free structure is remarkable; moreover, this antiferromagnetic state coexists with two-dimensional electron gas on the top surface of LaAlO3, which originates from out-of-plane charge transfer mainly between the La-d3z2−1 state at the surface and Cu-eg states in the CuO2 plane. In addition, a possible SrTiO3 capping layer is introduced in which, instead of La-d3z2−1, Ti-t2g orbitals exchange holes with electrons of Cu-eg orbitals.